Efficacy of TKIs in non-small cell lung cancer with atypical EGFR p.L747P and p.L747S mutations - Hu, Qiongxia; Wang, Jing; Jiang, Juan; Deng, Zhujun; Xie, Kang; Zhang, Wengeng; Li, Weimin; Chen, Bojiang (Frontiers in Oncology, 2026)
ObjectivesEpidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are established first-line treatments for advanced non-small cell lung cancer (NSCLC) harboring common sensitizing EGFR mutations, such as exon 19 deletions (19del) and the exon 21 p.L858R point mutation. However, evidence regarding the efficacy of first-, second-, and third-generation EGFR-TKIs against uncommon EGFR exon 19 mutations, specifically p.L747P and p.L747S, remains limited, and the underlying mechanisms are not fully elucidated. This study aimed to evaluate the clinical efficacy of different-generation EGFR-TKIs in NSCLC patients harboring EGFR p.L747P or p.L747S mutations by integrating our institutional cases with published evidence.Materials and methodsWe identified patients with NSCLC harboring EGFR p.L747P or p.L747S mutations detected by next-generation sequencing (NGS) between 2020 and 2025 and retrospectively collected their clinical data. A literature review was conducted to identify and integrate relevant published case data.ResultsAmong seven treated stage IV NSCLC patients with the p.L747P mutation, two who received second-generation EGFR-TKIs as first-line therapy had an objective response rate (ORR) of 0% and experienced rapid disease progression. In contrast, six patients received third-generation EGFR-TKIs as first- or second-line therapy, with two achieving stable disease (SD) and one achieving partial response (PR), with a substantially longer progression-free survival (PFS) of 12 to 40 months. Separately, six patients were found to harbor the p.L747S mutation concomitantly with a common TKI-sensitive mutation, none of whom had received prior EGFR-TKI therapy. Of these, two patients were treated with a third-generation TKI: 1 achieved SD and the other achieved partial response (PR).ConclusionsThis integrated retrospective analysis suggests that third-generation EGFR-TKIs may provide disease control (PR/SD) and prolonged PFS in a subset of NSCLC patients harboring uncommon EGFR p.L747P or p.L747S mutations, particularly those with co-existing sensitizing mutations or central nervous system metastases (CNS).